Multifunctional high strength and high energy epoxy composite structural supercapacitors with wet-dry operational stability1. Issue 40 (28th October 2015) - Westover, Andrew S.; Baer, Bradly; Bello, Babatunde H.; Sun, Haotian; Oakes, Landon; Bellan, Leon M.; Pint, Cary L.
<x xml:space="preserve">Abstract</x> An epoxy-composite reinforced structural supercapacitor is described with unpackaged performance integrity even under periods of extreme wet-dry water immersion.